The habitat of Paracoccidioides brasiliensis : how far from solving the riddle? (2001)
ABSTRACT: When trying to understand the pathophysiology of any infectious agent, one key piece of information is the determination of its habitat. In the case of Paracoccidioides brasiliensis , the precise location of the fungus’ environmental niche remains unde ned despite the efforts of various research groups. This review summarizes recent studies on the ecology of P. brasiliensis and certain facets of paracoccidioidomycosis. Studies on the juvenile form of paracoccidioidomycosis in children less than 13 years of age, the characterization of the ecological factors in the ‘reservarea’ where the infection is acquired and the presence of P. brasiliensis in the nine-banded armadillo (Dasypus novemcinctus), are all helping to pinpoint the microniche of this pathogen. The application of molecular biology techniques based on the ampli cation of nucleic acids will also hopefully help in establishing the precise habitat of P. brasiliensis.